Profiling Smallholder Farmers Goals and Aspirations for Enhanced Agricultural Development: a Case of Smallholder Maize Farmers - Oyedokun, Fakunle Olufemi; Leocadia, Zhou (Journal of Economics and Behavioral Studies, 2017)
The intervention of government in the development of smallholder agriculture is still grappling and has not yielded the desired results, despite the huge investment from government. This has been a source of concern to government and policy makers. This paper sought to analyze the socio-demographic features of the smallholder maize farmers; profile the goals and aspirations of these farmers; and lastly, to analyze the technical efficiency of maize farmers. Qamata and Tyefu in the Transkei and Ciskei homelands, respectively were purposively chosen for the study. Descriptive statistics; Principal component analysis (PCA) and stochastic frontier analysis (SFA) were used in the analysis. The result shows, that majority (66%) of the farmers were males with an average range of 61 years old. On the other hand, the PCA indicated that there is a variation between predicted goals and aspiration among maize farmers. The SFA result showed that farmers were efficient. The mean technical efficiency estimates up to 100%, an indication that farmers are more efficient in the usage of factors of production at their disposal in the study area. This implies that smallholder maize farming is lucrative due to its profit-making potentials. Moreover, this is a clear indication that more income and wealth is generated thereby implying that it is strategic and pivotal in improving farmers’ livelihoods